A social network approach to particles in Singapore English - Botha, Werner (2020)
This article discusses the findings of research on the use of particles in the vernacular speech of university students in Singapore, with particular reference to language variation and how meaningful social information is conveyed through the use of such particles. One key argument here is that the particles may be used to indicate speaker identity at the individual level, and across the Singapore speech community. This study draws on an adapted form of social network theory, and uses vernacular data to capture the dynamics underlying particle variation and therole these play in the construction of ‘Singapore English’.